Recovery of whole mitochondrial genome from compromised samples via multiplex PCR and massively parallel sequencing. (24th August 2018) - Hickman, Maureen P; Grisedale, Kelly S; Bintz, Brittania J; Burnside, Erin S; Hanson, Erin K; Ballantyne, Jack; Wilson, Mark R
In forensic casework, compromised samples often possess limited or degraded nuclear DNA, rendering mitochondrial DNA a more feasible option for forensic DNA analyses. The emergence of massively parallel sequencing (MPS) has enabled the recovery of extensive sequence information from very low quantities of DNA. We have developed a multiplex PCR method that amplifies the complete mitochondrial genome in a range of forensically relevant samples including single cells, cremated remains, bone, maggot and hairs isolated from dust bunnies. Following library preparation, MPS yields complete or nearly complete mitochondrial genome coverage for all samples. To confirm concordance between sample types and between sequencing platforms, we compared sequencing results from hair and buccal swabs from two references. Low initial DNA input into the multiplex PCR allows for conservation of precious DNA while MPS maximizes recovery of genetic information. Lay abstract: Compromised samples are routine in forensic casework, and evidence DNA is often limited and/or degraded. Mitochondrial DNA is often a suitable option for forensic analysis as it is available in multiple copies per cell. We have established a method that amplifies the complete mitochondrial genome in a range of compromised samples and utilizes new high-throughput sequencing technologies to recover maximal genetic information from a small amount of sample. Combination of the aforementioned amplification method and high-throughput sequencing allows the analyst to conserve DNA in forensic cases where DNA is often limited.